2021
DOI: 10.3389/fmolb.2021.699222
|View full text |Cite
|
Sign up to set email alerts
|

Selective Nutrient Transport in Bacteria: Multicomponent Transporter Systems Reign Supreme

Abstract: Multicomponent transporters are used by bacteria to transport a wide range of nutrients. These systems use a substrate-binding protein to bind the nutrient with high affinity and then deliver it to a membrane-bound transporter for uptake. Nutrient uptake pathways are linked to the colonisation potential and pathogenicity of bacteria in humans and may be candidates for antimicrobial targeting. Here we review current research into bacterial multicomponent transport systems, with an emphasis on the interaction at… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
26
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 35 publications
(26 citation statements)
references
References 104 publications
(134 reference statements)
0
26
0
Order By: Relevance
“…Among the 117 periplasmic proteins annotated, treatment with US-270 caused changes to the expression of 48 of them (14 upregulated, 34 downregulated), whereas US-90 and US-360 caused the upregulation of only 4 and 6 of them, respectively. These periplasmic proteins can specifically bind nutrients, such as amino acids, sugars, and other compounds ( Davies et al, 2021 ; Suginta et al, 2018 ). These results lend compelling support to the idea that bacteria can respond to osmotic stress by releasing periplasmic proteins outside their cells.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Among the 117 periplasmic proteins annotated, treatment with US-270 caused changes to the expression of 48 of them (14 upregulated, 34 downregulated), whereas US-90 and US-360 caused the upregulation of only 4 and 6 of them, respectively. These periplasmic proteins can specifically bind nutrients, such as amino acids, sugars, and other compounds ( Davies et al, 2021 ; Suginta et al, 2018 ). These results lend compelling support to the idea that bacteria can respond to osmotic stress by releasing periplasmic proteins outside their cells.…”
Section: Resultsmentioning
confidence: 99%
“…Such as vitamin B 12 import system permease protein (BtuC), peptide transporter ATP-binding protein (SapF), amino acid ABC transporter permease (GltJ), phosphate transport system permease protein (PstC). This massive upregulation of ABC transporter proteins would accelerate the transport of vitamin B12, peptides, amino acids, and phosphates ( Davies et al, 2021 ). Yet some of ABC transporter-related DEPs were downregulated by the HIU treatment; Such as oligopeptide ABC transporter substrate binding protein (OppA), glutamine ABC transporter substrate binding protein (GlnH), and maltodextrin binding protein (MalE) were all downregulated.…”
Section: Resultsmentioning
confidence: 99%
“…Future work is needed to advance understanding of the evolutionary processes that have resulted in the generation of these largely differing SBP repertoires and to characterize and understand the reasons for the observed SBP redundancy in many strains. Furthermore, the inhibition of ligand binding to SBPs has been shown to be an efficient approach to combat pathogens ( 36 , 55 ), and in this context, this study may be helpful for the development of approaches to fight pathogens of human, animal, and plant relevance.…”
Section: Discussionmentioning
confidence: 95%
“…Previous studies revealed a link between genome size, the number of ABC transport systems, and bacterial lifestyle ( 35 ). Furthermore, a relation between transport systems and the bacterial habitat was observed, showing that TRAP systems are more frequent in deep-sea and saline environments ( 36 ). However, we did not observe any obvious correlation of the SBP profile with either lifestyle ( Fig.…”
Section: Discussionmentioning
confidence: 99%
“…Many Gram-positive bacterial lipoproteins are substrate-binding proteins of ABC transporter systems responsible for the acquisition of multiple nutrients including amino acids and short peptides, sugars, polyamines, and many metal ions (Nguyen et al, 2020). It is also known that acquisition and metabolism of carbohydrates are essential for host colonization and pathogenesis of bacterial pathogens (Davies et al, 2021; Tan et al, 2015). Since the MMSYN1-0180-0186 genes are present in the same operon (MMSYN1-0179 is transcribed by itself, data not shown), they might function together contributing with the synthetic cell adherence to the cell host.…”
Section: Discussionmentioning
confidence: 99%